2018
DOI: 10.1016/j.ejvs.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of Thrombotic Events Following Endovenous Thermal Ablation of the Great Saphenous Vein

Abstract: Thrombotic events occur infrequently following GSV EVTA. Given the large numbers of procedures worldwide and the potential for serious consequences, further research is needed on the burden of these complications and their management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 56 publications
1
38
0
3
Order By: Relevance
“…Moreover, they may be performed without or with local anesthesia only. Hence, the minimally/less invasive methods allow early mobilization and fast patient return to daily and working activity; thus, their use is associated with a reduced risk of post-operative thrombosis [30,32,33]. Regrettably, despite the aforementioned benefits for the patient, when assessed in regards to the rate of disease recurrence, all these methods have substantially similar effectiveness in long-term assessment [14,[16][17][18]34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they may be performed without or with local anesthesia only. Hence, the minimally/less invasive methods allow early mobilization and fast patient return to daily and working activity; thus, their use is associated with a reduced risk of post-operative thrombosis [30,32,33]. Regrettably, despite the aforementioned benefits for the patient, when assessed in regards to the rate of disease recurrence, all these methods have substantially similar effectiveness in long-term assessment [14,[16][17][18]34].…”
Section: Discussionmentioning
confidence: 99%
“…ETA is recommended as the first-choice procedure for symptomatic varicose veins. 9) Since the therapeutic goal of ETA is the obliteration of incompetent saphenous veins by thermal injury to the venous wall, ETA could be associated with concerns regarding the potential risks for VTE. Japanese nationwide survey found that venous thrombotic events, including VTE (deep vein thrombosis (DVT), pulmonary thromboembolism (PTE), and EHIT class 3-4), occurred in 0.194% of 43,203 cases.…”
Section: Discussionmentioning
confidence: 99%
“…If a thrombus forms postoperatively at the proximal junction of the treated vein, it is called endovenous heat-induced thrombosis (EHIT) in the international literature; if it extends into the deep vein system, it is called postablation superficial thrombus extension (PASTE) [407][408][409]. Schäffer et al indicate that this clinical constellation is independent of the procedure used and can appear even after nonthermal procedures; furthermore, it refers to a thrombus extension in the deep and not the superficial vein system.…”
Section: Recommendation 114mentioning
confidence: 99%
“…Sect. 6.2.2.2.2.1 PATE after EVLA -Burns [454] -Deep leg vein thrombosis [409,454,455] -Lung embolism [409,455] -In individual cases: lymphocele, wound infection, arteriovenous fistula [349,386] The incidence of paraesthesia after sRFA in the European cohort study was 3.4% in the first postoperative week, and then it fell to 0.4% and remained at that value throughout the 5-year observation period [451,456]. This represents a clear improvement over previous treatment procedures [351].…”
Section: Radio Frequency-induced Segmental Thermal Ablation/segmental...mentioning
confidence: 99%